2015
DOI: 10.1080/09168451.2014.997186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Korean Red Ginseng extract on hepatic lipid accumulation in HepG2 cells

Abstract: Korean Ginseng, the root Panax ginseng CA Meyer, has been widely used as a traditional herbal medicine in East Asian countries. In this study, we investigated the effects of Korean Red Ginseng water extract (KRGE) on hepatic lipid accumulation in HepG2 cells. First, we investigated the cytotoxic effects of KRGE on HepG2 cells. Cytotoxicity was unaffected in the concentrations of 1–50 μg/ml of KRGE.Intracellular lipid accumulation was assessed by the quantification of intracellular triglyceride and cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Numerous in vitro research reports have documented that ginseng and ginsenosides can activate the AMPK pathway resulting in increased levels of p-AMPK and phospho-acetyl-CoA carboxylase in hepatocyte HepG2 cells [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ( Table 1 ). By activating this pathway, ginseng and ginsenosides can, in vitro , suppress the expression of fatty acid synthase (FAS), 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGCR), phosphoenolpyruvate carboxykinase (PEPCK), and glucose 6-phosphatase (G6Pase)—thereby inhibiting TAG synthesis [27] , [28] , [31] , cholesterogenesis [28] , [33] , and gluconeogenesis [29] , [30] , [34] .…”
Section: Effect On Livermentioning
confidence: 99%
“…Numerous in vitro research reports have documented that ginseng and ginsenosides can activate the AMPK pathway resulting in increased levels of p-AMPK and phospho-acetyl-CoA carboxylase in hepatocyte HepG2 cells [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ( Table 1 ). By activating this pathway, ginseng and ginsenosides can, in vitro , suppress the expression of fatty acid synthase (FAS), 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGCR), phosphoenolpyruvate carboxykinase (PEPCK), and glucose 6-phosphatase (G6Pase)—thereby inhibiting TAG synthesis [27] , [28] , [31] , cholesterogenesis [28] , [33] , and gluconeogenesis [29] , [30] , [34] .…”
Section: Effect On Livermentioning
confidence: 99%
“…Alcoholic fatty liver is a uniform response by the liver toward alcohol that can progress, resulting in increasingly severe liver diseases. Despite the growing body of literature on the functionality of KRG [19,20], the preventive effects of ginseng against alcohol-induced fatty liver in vivo and the underlying mechanism responsible for it remain unclear. Therefore, in the present study, we tested the hypothesis that KRG has a preventive effect against alcoholic fatty liver, focusing on the role of lipid metabolic homeostasis at the liver-adipose tissue axis.…”
Section: Resultsmentioning
confidence: 99%
“…showed that ginsenoside Rb1 regulates appetite and achieves energy balance by modulating the expression of inflammatory factors in vivo and restoring the anorexigenic effects of leptin and leptin p-STAT3 Frontiers in Pharmacology frontiersin.org signaling in the hypothalamus in mice fed a high-fat diet. In vitro studies have shown that ginsenosides can inhibit triglyceride synthesis, cholesterol production (Lee et al, 2015), gluconeogenesis (Quan et al, 2012) by activating AMPK and inhibiting fatty acid synthase (FAS) and 3-hydroxy-3-methyl-glutaryl coenzyme A reductase (HMGCR). Ginseng reduced adipocyte size and fat storage in highfat diet-induced obese mice and rats (Lee et al, 2010).…”
Section: Discussionmentioning
confidence: 99%